Russian grotesque realism : the great reforms and the gentry decline - Kokobobo, Ani (The Ohio State University Press, 2018)
"A rereading of the Russian realist novel that proposes a hybrid genre, grotesque realism, to describe changes during the postreform era"-- Provided by publisher
Keywords: Russian fiction -- 19th century -- History and criticism.; Grotesque in literature.; Realism in literature.; Gentry in literature.; Roman russe -- 19e siècle -- Histoire et critique.; Grotesque dans la littérature.; Réalisme dans la littérature.; LITERARY CRITICISM -- Russian & Former Soviet Union.; LITERARY CRITICISM -- General.; Gentry in literature; Grotesque in literature; Realism in literature; Russian fiction; 1800-1899; Criticism, interpretation, etc.